Saudi Arabian preschool teachers’ perceptions, positive and negative experiences of play-based robotics activities - Dalal Aldhilan; Shahid Rafiq; Ayesha Afzal (Cogent Education)
This study explores Saudi Arabian preschool teachers’ perceptions, experiences and challenges in integrating play-based robotics activities into early childhood education. Employing a qualitative case study design within a constructivist paradigm, interviews with 37 teachers provide insights into both the benefits and obstacles associated with educational robotics. Findings reveal that teachers generally hold positive attitudes toward play-based robotics, highlighting its role in fostering critical thinking, creativity and Science, Technology, Engineering and Mathematics (STEM) literacy. They report increased student engagement, cross-curricular learning and enhanced motivation. However, challenges, such as budget constraints, technical difficulties and cultural resistance hinder effective implementation. To address these barriers, the study underscores the need for ongoing professional development, inclusive curriculum alignment and strategic institutional support. By contributing to global discussions on technology integration in early childhood education, this research provides valuable insights for educators, policymakers and researchers, particularly in culturally diverse educational settings. The findings offer guidance on fostering effective and sustainable use of robotics in preschool education across various cultural and institutional landscapes.